Reference hyperlinked to the source: A step-by-step guide for creating hyperlinks in references - N Shah, Jay; Malla, Ashesh; Jaiswal, Sunil; Shah, Sanjeeb; Gupta, Abhishek (Journal of Chitwan Medical College, 2024)
Hyperlinking is an essential component of manuscript writing that helps readers, authors, reviewers, and editors navigate the online content. Correct hyperlinking enhances the quality, accessibility, and credibility of the manuscript. This editorial summarizes an easy way to add hyperlinks to the references which would be helpful in manuscript writing.